THE EFFORTS TO IMPROVE TEACHER PERFORMANCE THROUGH ACADEMIC SUPERVISION BY THE PRINCIPAL IN PRIMARY SCHOOL - Kasirin Kasirin (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2020)
There have been many attempts to prepare teachers to become professionals. The fact shows that not all teachers have a good performance in carrying out their duties. Supervision, which is assumed to be a teacher guidance service, is expected to advance and develop teaching so that teachers can teach well and impact student learning. The research aims to improve teacher performance through academic supervision by the principal at SDN 7 Sungai Ambawang. The research method used was descriptive research, with school action research with a collaborative nature with the teacher. The subjects in this study were 18 teachers at SDN 7 Sungai Ambawang, Sungai Ambawang District. Data collection technique in this study was measurement technique and the instrumentl used was the observation sheet. This study's results are as follows: The first finding, the teacher's performance increases in doing learning planning. The second finding, the teacher's performance increases in carrying out learning. The third finding, the teacher's performance increases in assessing student learning achievement. To improve teacher performance at SDN 7 Sungai Ambawang has been done well. Researchers provide motivation, guidance, and direction to teachers to compile complete teaching administration and teaching planning through academic supervision to produce higher quality learning. (2) In the implementation of academic supervision to improve teacher performance at SDN 7 Sungai Ambawang, almost all of the 18 teachers could carry out learning well. Academic supervision activities can increase teacher competence in preparing and implementing learning well, creatively, and fun.